Regular and lightweight mobility management in the HIP-based M2M overlay network. (2016) - Dhraief, Amine; Belghith, Abdelfettah; Drira, Khalil
The host identity protocol-based (HIP) machine-to-machine (M2M) overlay network is a virtual, self-organised and secure M2M network build on the top of the internet. M2M devices forming this overlay network may change their point of attachment to the overlay while having running sessions. HIP provides a native mobility support to these M2M devices. However, this support is not adapted for the M2M context. We propose in this paper a regular and lightweight mobility strategies to efficiently handle M2M devices mobility within this overlay. We first analytically assess the signalling cost of the regular and lightweight mobility strategies. Then, we evaluate the application recovery time of an M2M device experiencing a mobility episode through simulation. Both signalling cost analysis and simulation results show that our lightweight mobility strategy significantly out-performs regular HIP.